Right Heart Thrombi Accompained with Pulmonary Embolism - Mustafa Çörtük; Selahattin Akyol; Kemal Kiraz (Düzce Tıp Fakültesi Dergisi, 2015)
Aim: Right sided heart thrombus (RSHT) is rarely seen. It is generally detected during transthoracic echocardiographic (TTE) examination or multislice thoracic computed tomographic scanning for pulmonary embolism (PE). Although RSHT and PE secondary to this situation is rare, mortality during the course of process is very high. We aim to aproach right cardiac trombus and determine the results of treatment. Method: In this study 25 patients hospital records were investigated retrospectively. The data obtained consisted of diagnostic methods, presence of shock state, treatments applied and results were assessed. Results: Th present study revealed that the 32% of patients had been admitted to hospital in shock state, hospital mortality rate was 24%, and this mortality rate was not affected by different treatment choices. Conclusion: The exact incidence of RSHT is unknown. It is reported that the probability of seeing a case suffering from RSHT during echocardiographic examination performed to diagnose the PE is 9%. RSHT may cause PE anytime and requires urgent treatment. In our study, we determined that the hospital mortaliy did not change with the type of given treatment and overall mortality was determined as 24%. There are no sufficient studies searching large series on RSHT in literature. Therefore, there is no agreement on treatment tecniques.